In Vivo Effects of Lattice Radiation Therapy on Local and Distant Lung Cancer: Potential Role of Immunomodulation - Kanagavelu, Saravana (Radiat Res, 2014)
Radiation is a potent immune-modulator that elicits cell death upon tumor, stromal and angiogenic compartments of tumor microenvironment. Here, we test a novel approach of high-dose radiation delivery using three dimensional volume based lattice radiation therapy (LRT) to understand the impact of different volume irradiation in eliciting both local and metastatic/distant tumor control through modulation of tumor immune micro-environment. To study such effects of LRT, tumors were implanted in both hind legs of C57BL/6 mice using Lewis lung carcinoma 1 (LLC1) cells. Mice were divided into five groups: untreated; partial tumor volume groups included two 10% vertices, one 20% vertex and one 50% vertex of the total tumor volume; and 100% open-field irradiation. Tumors implanted in the left flank were irradiated with a single dose of 20 Gy while the tumors in the right flank were unirradiated. Tumor growth and regression as well as immune responses (such as Th1 and Th2; T-cell infiltration) were determined after radiation treatment. Results demonstrated that both 100% open-field irradiation and 20% volume irradiation (in two 10% volumes) resulted in significant growth delay in the irradiated tumor. Further, all types of radiation exposures, partial or 100% volume, demonstrated distal effectiveness, however, 20% volume irradiation (in two 10% volumes) and 50% tumor volume irradiation led to maximum growth delay. Mice treated with partial tumor volume radiation induced a robust IFN-γ and Th1 response when compared to whole-tumor irradiation and down-modulated Th2 functions. The presence of increased CD3(+) cells and TRAIL in partially irradiated tumor volumes correlated well with tumor growth delay. Further, serum obtained from any of the LRT treated mice caused growth inhibition of endothelial cells when compared to serum obtained from either untreated or open-field irradiated groups. These results indicate that high-dose partial volume irradiation can cause an improved distant effect than the total tumor volume irradiation through activating the host immune system.